2013
DOI: 10.1111/ger.12045
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the presence of atrophic tongue in patients with dry mouth

Abstract: High Candida CFU, low stimulated saliva flow rate and advanced age were identified as closely associated factors for the risk of development of atrophic tongue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
1
12
0
2
Order By: Relevance
“…By linking these oral pathologies with xerostomia, a significant relationship only with atrophic tongue, and denture stomatitis was found. This finding is in concordance with Kimori et al (28) , who found a high Candida CFUs, low stimulated saliva flow rate and advanced age were identified as closely associated factors for the risk of development of atrophic tongue. On the other hand, Nakamura et al (33) , reported C. albicans was associated with atrophic glossitis in xerostomia patients who had no systemic predisposing factors, indicating that C. albicans remains a treatment target for Candida-related atrophic glossitis.…”
Section: Significant Associations Were Considered With a P < 005supporting
confidence: 93%
See 2 more Smart Citations
“…By linking these oral pathologies with xerostomia, a significant relationship only with atrophic tongue, and denture stomatitis was found. This finding is in concordance with Kimori et al (28) , who found a high Candida CFUs, low stimulated saliva flow rate and advanced age were identified as closely associated factors for the risk of development of atrophic tongue. On the other hand, Nakamura et al (33) , reported C. albicans was associated with atrophic glossitis in xerostomia patients who had no systemic predisposing factors, indicating that C. albicans remains a treatment target for Candida-related atrophic glossitis.…”
Section: Significant Associations Were Considered With a P < 005supporting
confidence: 93%
“…Studies have attributed a higher prevalence of oral candidiasis denture stomatitis, atrophic tongue, dysgeusia, fissured tongue, associated with both hyposalivation and xerostomia (3,7,9,18,28) . Because of thus, the purpose of this study was to identify the risk factors of xerostomia and hyposalivation in senior people; 60 years and older, and to investigate the association with medication, habits and other oral complications.…”
Section: Relationship Between Xerostomia and Hyposalivation In Seniormentioning
confidence: 99%
See 1 more Smart Citation
“…When the attending dentist could not determine the amount of papillary atrophy, a consensus was reached by discussion with an oral surgeon (Y.N.) with 30 years of experience [ 7 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Other etiological factors of atrophic glossitis include hyposalivation and candidiasis [ 2 , 4 6 ]. An increase in Candida colony counts, a low salivary flow rate, and advanced age were identified as being risk factors that were closely associated with the development of atrophic glossitis [ 7 , 8 ]. However, the Candida species that are the most relevant to the development of atrophic glossitis remain unclear.…”
Section: Introductionmentioning
confidence: 99%